EFEKTIVITAS PENYULUHAN MENGGUNAKAN LAGU “GIGI SEHAT” TERHADAP PENURUNAN PLAK DI BARITO KUALA (Tinjauan SDN Barangas Timur 1 Kecamatan Alalak Kabupaten Barito Kuala) - Faulina Windiyana; Rosihan Adhani; Aulia Azizah (Universitas Lambung Mangkurat, 2020)
ABSTRAK Background: Basic Health Research Results (Riskesdas) in 2018 showed the dental and oral health problems of the people in Indonesia reached 57.6%, while the dental and mouth problems in the province of South Kalimantan in children aged 5-9 years amounted to 71.17%, the daily brushing behavior amounted to 96.04% but the correct brushing time is only 4.97%. This indicates that there is still a lack of knowledge about how and when to brush the teeth properly and correctly so it needs an innovation in providing information in this is necessary. The counseling by using the songs is expected to change a person's behavior in ways and when they’re brushing their teeth properly. Objective: To analyze the effectiveness of the counseling using the